Clinical Experience of Personalized Phage Therapy Against Carbapenem-Resistant Acinetobacter baumannii Lung Infection in a Patient With Chronic Obstructive Pulmonary Disease - Tan, Xin; Chen, Huaisheng; Zhang, Min; Zhao, Ying; Jiang, Yichun; Liu, Xueyan; Huang, Wei; Ma, Yingfei (Frontiers in Cellular and Infection Microbiology, 2021)
Overuse of antibiotics in clinical medicine has contributed to the global spread of multidrug-resistant bacterial pathogens, including Acinetobacter baumannii. We present a case of an 88-year-old Chinese man who developed hospital-acquired pneumonia caused by carbapenem-resistant A. baumannii (CRAB). A personalized lytic pathogen-specific single-phage preparation was nebulized to the patient continuously for 16 days in combination with tigecycline and polymyxin E. The treatment was well tolerated and resulted in clearance of the pathogen and clinical improvement of the patient’s lung function.